Energetic and exergetic analysis of a new compact trigeneration system run with liquefied petroleum gas - Perez, Nestor Proenza [UNESP]; Sadamitsu, Marlene Titosse [UNESP]; Silveira, Jose Luz [UNESP]; Antunes, Julio Santana [UNESP]; Tuna, Celso Eduardo [UNESP]; Valle, Atilio Erazo [UNESP]; Silva, Natalia Faria [UNESP] (Elsevier B.V., 2015)
In this study, the first and second laws of thermodynamics are used to analyze the quantity and quality of energy in a small compact trigeneration system. This combined cycle is composed of a little reciprocating ICE model GM, 1.0 CORSA (internal combustion engine), using LPG (liquefied petroleum gas) as fuel, HE1 and HE2 (two heat exchangers) and an AM (absorption machine) using ammonia water as working fluid mixture. The mass and energy balance equations of the engine and subsystems are reviewed in detail. Exergy of each involved stream is calculated and the exergetic balance of each subsystem is presented, as well as the global system, identifying where and why losses and irreversibilities occurs. Efficiencies based on the second law of thermodynamics are calculated for each subsystem and compared. Special attention is given to identification and quantification of second law efficiencies and the irreversibilities of various processes and subsystems. The determination of the irreversibilities in each subsystem is particularly important since they are not identified in traditional first law analysis. Furthermore, this study revealed that the combustion was the most important contributor to the system inefficiency representing 36.0% of the total exergy input and 73% of the total exergy destruction. The exergetic efficiency of the trigeneration system is determined to be 51.19%. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Cogeneration; Energetic; Exergetic; Internal combustion engine; Efficiencies